Liposomal T cell engager and re-director for tumor cell eradication in cancer immunotherapy - Fang Xie; Luchen Zhang; Sanyuan Shi; Anjie Zheng; Jiaxing Di; Shanshan Jin; Xuguang Miao; Fenglan Wu; Xiaolong Chen; Yanhong Zhang; Xiaohui Wei; Yuhong Xu (Taylor & Francis Group, 2022)
T cells are one of the most important effector cells in cancer immunotherapy. Various T cell-dependent bispecific antibody (TDB) drugs that engage T cells for targeted cancer cell lysis are being developed. Here, we describe supra-molecular T-cell redirecting antibody fragment-anchored liposomes (TRAFsomes) and report their immune modulation and anti-cancer effects. We found that TRAFsomes containing different copies of anti-CD3 fragments displayed different T cell modulation profiles, showing that optimization of surface density is needed to define the therapeutic window for potentiating cancer cell-specific immune reactions while minimizing nonspecific side effects. Moreover, small molecular immunomodulators may also be incorporated by liposomal encapsulation to drive CD8 + T cell biased immune responses. In vivo studies using human peripheral blood mononuclear cell reconstituted mouse models showed that TRAFsomes remained bounded to human T cells and persisted for more than 48 hours after injection. However, only TRAFsomes containing a few anti-CD3 (n = 9) demonstrated significant T cell-mediated anti-cancer activities to reverse tumor growth. Those with more anti-CD3s (n = 70) caused tumor growth and depletion of human T cells at the end of treatments. These data suggested that TRAFsomes can be as potent as traditional TDBs and the liposomal structure offers great potential for immunomodulation and improvement of the therapeutic index.Abbreviation: Chimeric antigen receptor T cells (CAR-T cells), Cytokine release syndrome (CRS) Cytotoxic T cell (CTL) Effector: target ratios (E:T ratios), Heavy chain (HC) Immune-related adverse events (irAE), Large unilamellar vesicle (LUV), Peripheral blood mononuclear cells (PBMCs, Single-chain variable fragment (scFv), T cell-dependent bispecific antibody (TDB), T cell redirecting antibody fragment-anchored liposomes (TRAFsomes), Methoxy poly-(ethylene glycol) (mPEG)